Sykepleieforskning i rurale områder i Norge; en scoping review - Svenja Eidesen De Smedt; Grete Mehus (Septentrio Academic Publishing, 2017)
In Norway, many areas can be classified as rural on climatic, geographic or demographic grounds. The rural context means that nurses and patients face circumstances and situations that are different, or do not occur in urban areas. The aim of this study was to identify existing research literature to ascertain what is known about nursing in rural areas of Norway. Scoping review, following Arksey and O`Malley`s methodological framework was used. A total of 111 articles were identified from searching five databases, twenty articles were included. This study gives an overview of rural descriptions and also provides a geographic presentation of areas categorized as rural in existing Norwegian nursing research. Only eight of the twenty articles described the rural context. The lack of descriptions makes it difficult to compare and conclude on causal relationships in the field. Increased awareness and more research into challenges that confront patients and nurses in rural settings in Norway is needed.